Characterization of milk composition in narrow‐ridged finless porpoises (Neophocaena asiaeorientalis) at different lactation stages. Issue 3 (9th February 2017) - Zeng, Xianyuan; Huang, Shiang‐lin; Qian, Zhengyi; Hao, Yujiang; Wang, Ding; Ji, Junhua; Nabi, Ghulam
Abstract: Lactation plays a vital role in reproductive success, evolving with ecological adaptations of mammalian life histories. Knowledge of the lactation process in odontocetes is scarce and limited to a handful of species. We investigated the changes in milk composition across different lactation stages, including prepartum mammary secretion and early, mid‐ and late lactation of narrow‐ridged finless porpoises. Prepartum mammary secretion was greenish and characterized by high protein, low sugar, and negligible fat contents. In contrast, milk fat became predominant over protein and sugar contents throughout all lactation stages. At the early lactation stage, the contents of all milk constituents except water varied greatly. At the mid‐late lactation stage, the gross milk composition was relatively stable and was composed of, on average, 67.34% ± 4.13% water, 9.96% ± 0.75% protein, 21.40% ± 3.24% fat, and 1.72% ± 0.73% sugar. Our findings provide new insight into milk composition at different lactation stages in the narrow‐ridged finless porpoise.